FUNGSI HUKUM PARIWISATA DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH - Dewa Gde Rudy (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
Micro, Small and Medium Enterprises (UMKM) have a very strategic role in national development, especially development in the field of tourism. The fact is that business activities carried out by UMKM often fail to compete with large businesses which are in a stronger position. Related to that, empowering UMKM in the field of tourism business is a very important thing to do. The discussion and research in this paper are focused on two things, First: how is the reality and empowerment of UMKM in the field of tourism business. Second: what is the function of tourism law in order to empower UMKM. In this paper, the normative legal research method is used, namely library legal research using a legislation approach (statue approach) and conceptual approach (conceptual approach). The results of the study show that the reality of UMKM in the field of tourism business is still in a marginalized position and still has limited access to capital, business information, marketing, and business opportunities which are important components in conducting business activities. The legal function of tourism in the context of empowering UMKM is ensuring certainty of the protection of UMKM, so that UMKM get various accesses related to businesses that are run to be able to develop and compete with large businesses.